A redox-responsive self-assembling COA-4-arm PEG prodrug nanosystem for dual drug delivery suppresses cancer metastasis and drug resistance by downregulating hsp90 expression - Yi Zhou; Yingling Miao; Qiudi Huang; Wenwen Shi; Jiacui Xie; Jiachang Lin; Pei Huang; Chengfeng Yue; Yuan Qin; Xiyong Yu; He Wang; Linghao Qin; et al. (Elsevier, 2023)
Metastasis and resistance are main causes to affect the outcome of the current anticancer therapies. Heat shock protein 90 (Hsp90) as an ATP-dependent molecular chaperone takes important role in the tumor metastasis and resistance. Targeting Hsp90 and downregulating its expression show promising in inhibiting tumor metastasis and resistance. In this study, a redox-responsive dual-drug nanocarrier was constructed for the effective delivery of a commonly used chemotherapeutic drug PTX, and a COA-modified 4-arm PEG polymer (4PSC) was synthesized. COA, an active component in oleanolic acid that exerts strong antitumor activity by downregulating Hsp90 expression, was used as a structural and functional element to endow 4PSC with redox responsiveness and Hsp90 inhibitory activity. Our results showed that 4PSC/PTX nanomicelles efficiently delivered PTX and COA to tumor locations without inducing systemic toxicity. By blocking the Hsp90 signaling pathway, 4PSC significantly enhanced the antitumor effect of PTX, inhibiting tumor proliferation and invasiveness as well as chemotherapy-induced resistance in vitro. Remarkable results were further confirmed in vivo with two preclinical tumor models. These findings demonstrate that the COA-modified 4PSC drug delivery nanosystem provides a potential platform for enhancing the efficacy of chemotherapies.